Controls of Deep-Seated Faults and Folds on Hydrocarbon Fluid Migration and Accumulation in Sedimentary Basins: A Case Study from the Northwestern Sichuan Basin, China. (24th December 2021) - Wang, Xi; Liu, Yin; Cao, Jian; Liu, Yiduo; Luo, Bing; Wu, Kongyou; Shi, Zheng; Kang, Hongbin
Abstract : Deep-seated faults and folds of foreland basin systems have become important exploration targets in the recent years because they are crucial in controlling fluid migration and hydrocarbon accumulation. In this study, we analyzed the characteristics and formation history of these structures in the northwestern Sichuan Basin using recently acquired two-dimensional (2D) and three-dimensional (3D) seismic data. The seismic interpretation revealed that the thrust sheets, tectonic wedges, and foredeep were well developed in the northwestern Sichuan Basin from the mountain to the basin. Forward thrusts, fault-bend folds, and wedges are the main types of structures in the thrust sheets and tectonic wedges. The deep-seated faults and folds were easily recognized in the high-resolution 3D seismic data. The imbricate thrust faults that merged into detachment layers of the Lower Cambrian are the main types of structures in the foredeep, and they show a prominent strike-slip influence in the horizontal direction. The formation of these structures in the foredeep in the northwestern Sichuan Basin mainly endured two stages of thrusting, including those during the Middle-to-Late Triassic and Cenozoic. Based on the tectonic evolution and seismic data, we infer that these deep-seated faults and folds in the foredeep may have formed earlier than the northern Longmen Shan fold-and-thrust belts and they may have been initially active in the late of Early Triassic and reactive during the Cenozoic. Furthermore, evaporites in the Lower and Middle Triassic were crucial in forming these structures. The petroleum exploration data suggested that the deep-seated faults can facilitate hydrocarbon accumulation. The thrust faults in the foredeep were more likely to act as migration pathways for fluids instead of sealing barriers along the horizontal direction. The interconnected reservoirs of deep-seated folds possess a great potential to allow large-scale hydrocarbon accumulation. Our study provides a good example for evaluating the hydrocarbon exploration potential in the deeply buried area in the sedimentary basin.